Materialismo, simplicidade voluntária e decrescimento: vida de rico ou vida rica? - Paiva, Marlon Bruno Matos (2020)
This thesis aimed to analyze the relationship between consumer intention and behavior regarding voluntary reduction of consumption (degrowth). The theoretical framework of the research presented concepts about sustainable attitude and behavior, fundamentals of degrowth and issues related to consumption, well-being and lifestyle, focusing on the connection between sustainability, voluntary simplicity and materialism. In order to achieve the research goals, we performed several multivariate analysis: sociodemographic and psychographic analysis on consumers profile; descriptive analysis of the constructs: degrowth, voluntary simplicity and materialism; exploratory and confirmatory factor analysis of the constructs in order to validate the scale; multigroup analysis to verify the research consistency in different samples; and also, evaluation of the theoretical model through structural equation modeling. We have developed the “Perceptions about Degrowth” scale, with eighteen items divided into six factors that allow verifying the behavioral intention to engage to degrowth. The structural model and the correlation between the constructs presented a strong positive link between voluntary simplicity and intention to engage to degrowth, as well as a strong negative connection between materialism and intention to engage to degrowth. The thesis also made it possible to find eight different profiles, based on cognition, affection and behavior related to voluntary reduction of consumption. Given some profiles are unaware, lacks affection or behavior towards degrowth, actions are required to make consumer behavior even more focused on sustainability issues, with a greater emphasis on proximity, justice and citizenship, R’s cycle, reduction of production and consumption, caring for others and environmental responsibility, thus achieving the necessary transition to a sustainable consumer society.